L'ingegneria del vento Un'antica, modernissima scienza - Briganti, Daniele (Pluriverso - Quaderni della Biblioteca del Polo Universitario di Prato, 2006)
The volume aims to give the most comprehensive answer to to the question "Why has wind engineering taken on such an important role today?". In their work, the authors proceed by stages. First, they accompany the readers on a historical journey, in which they led a reflection on the ineluctable relationship between man, civilisation and climate; subsequently, they highlight the socio-economic aspects of the phenomenon; finally, they bring to the reader's attention the research activity carried out in the Inter-University Research Centre on Building Aerodynamics and Wind Engineering, throwing a look at some of the engineering examples of the latest generation, which, by their nature, have a strong link with wind action.